Vascular contributions to cognitive impairment and dementia: Research consortia that focus on etiology and treatable targets to lessen the burden of dementia worldwide - Jordan T. Gladman; Roderick A. Corriveau; Stephanie Debette; Martin Dichgans; Steven M. Greenberg; Perminder S. Sachdev; Joanna M. Wardlaw; Geert Jan Biessels (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract The research into vascular contributions to cognitive impairment and dementia (VCID) aims to understand the importance of cerebrovascular biology in cognitive decline. Prevention and treatment of VCID is poised to have major impact on dementia‐related disease burden and is thus a critical emerging objective in dementia research. This article presents VCID consortia focused on multidisciplinary approaches to identify key pathologic targets and develop diagnostic tools with the goal of bridging the divide between basic research and clinical trials. Members of these multi‐institute, multidisciplinary consortia provide a prospective on the history and emerging science of VCID and how VCID consortia can address some of the more complex questions in VCID and drive the field forward. These consortia, and others like them, are uniquely suited to tackle some of the most difficult obstacles in translating research to the clinic.